Inflammatory Fibroid Polyp in a 48-Year-Old Male: A Rare Cause of Intussusception - Theresia Karuhanga; Caroline Ngimba; James J. Yahaya (Case Reports in Surgery)
Inflammatory fibroid polyp is a neoplastic condition affecting the gastrointestinal tract and particularly the gastric antrum. It is virtually a benign submucosal mass comprising mesenchymal cells and numerous small blood vessels with inflammatory cells and commonly eosinophils. Patients with inflammatory fibroid polyps usually present clinically with mechanical intestinal obstruction with or without intussusception. Herein, we present a case of a 48-year-old male with a known history of schizophrenia who presented with mechanical intestinal obstruction following intussusception due to inflammatory fibroid polyp involving the proximal jejunojejunal part of the jejunum.